Epidemiological Analysis of Trauma Patients following the Lushan Earthquake - Zhang, Li (Public Library of Science, 2014)
BACKGROUND: A 7.0-magnitude earthquake hit Lushan County in China’s Sichuan province on April 20, 2013, resulting in 196 deaths and 11,470 injured. This study was designed to analyze the characteristics of the injuries and the treatment of the seismic victims. METHODS: After the earthquake, an epidemiological survey of injured patients was conducted by the Health Department of Sichuan Province. Epidemiological survey tools included paper-and-pencil questionnaires and a data management system based on the Access Database. Questionnaires were completed based on the medical records of inpatients with earthquake-related injuries. Outpatients or non-seismic injured inpatients were excluded. A total of 2010 patients from 140 hospitals were included. RESULTS: The most common type of injuries involved bone fractures (58.3%). Children younger than 10 years of age suffered fewer fractures and chest injuries, but more skin and soft -tissue injuries. Patients older than 80 years were more likely to suffer hip and thigh fractures, pelvis fractures, and chest injuries, whereas adult patients suffered more ankle and foot fractures. A total of 207 cases of calcaneal fracture were due to high falling injuries related to extreme panic. The most common type of infection in hospitalized patients was pulmonary infections. A total of 70.5% patients had limb dysfunction, and 60.1% of this group received rehabilitation. Most patients received rehabilitation within 1 week, and the median duration of rehabilitation was 3 weeks. The cause of death of all seven hospitalized patients who died was severe traumatic brain injuries; five of this group died within 24 h after the earthquake. CONCLUSIONS: Injuries varied as a function of the age of the victim. As more injuries were indirectly caused by the Lushan earthquake, disaster education is urgently needed to avoid secondary injuries.